Pengaruh Persepsi Penggunaan Artificial Intelligence terhadap Kualitas Audit - Gultom, Melani Risma; Sari, Vita Fitria (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the influence of the perception of artificial intelligence ease of use and the perception of artificial intelligence usefulness on audit quality. Quantitative causality is the term for this type of research. A closed questionnaire was used to collect research data, which was then distributed via linkedIn, email, and whatsApp. The sampling method used was non-probability sampling, specifically convenience sampling, with a total of 121 valid respondents who were external auditors from Public Accounting Firms (KAP) in Indonesia. Because the data was obtained from easily accessible respondents, there is potential for sample bias that could affect the representativeness and external validity of the research findings. Data analysis was performed using multiple linear regression with SPSS version 26. The research results indicate that the perception of artificial intelligence usefulness has a positive and significant impact on audit quality, while the perception of artificial intelligence ease of use has a negative and non-significant impact on audit quality.